Einamasis fondų komplektavimas periodikos ir knygų mikrokopijomis - Urbonas, Viktoras (Knygotyra, 1972)
Libraries of the Lithuanian SSR receive books and periodicals printed on paper. Current acquisition of microcopies is still rare. In libraries microcopies of periodicals are represented only by some medical magazines. Acquisition of stocks and services to readers raise many difficulties and problems for libraries. Acquisition of microcopies of books and periodicals could help to solve some of those problems. For this purpose it is economic and expedient to multiply foreign magazines making microfilms instead of offset printing, to publish part of the number of copies printed of All-Union and republic newspapers, scientific magazines and serials in the form of microfilms. It has become necessary to multiply in microfiches foreign information literature and scientific books, required by the large libraries of the Soviet Union and the Lithuanian SSR. It is high time to organize publication of microfiche of those specialized scientific books, out-of-print publications, etc. which are not used widely and relief printing of which is not economic. It is necessary to organize publishing houses to issue microcopies of periodicals and books, to begin acquisition of foreign microfilms and microcards, to supply libraries with equipment necessary for a successful work with microcopies in our republic.